APLIKASI BEBERAPA DOSIS TRICHO-KOMPOS LEGUMINOSA TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN CABAI (Capsicum annuum L.) - Refli Junaidi; Fifi Puspita; Armaini ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Chilli (Capsicum annuum L.) is one of the horticultural commodities that have significant economic value, therefore the use of organic fertilizer or compost is indispensable in improving the productivity of chili, one of the organic fertilizer that is leguminose Tricho-compost. This research aims to determine the effect of multiple-dosage applications leguminose Tricho-compost and got a Tricho-compost of the best dosage leguminose Tricho-compost in enhancing the growth and productivity of chili plants (Capsicum annuum L.). The data were analyzed statistically using analysis of variance followed by Duncan's New Multiple Range Test (DNMRT) at the level of 5%. The results showed that the differences in the growth and productivity of chili plants of several dosage of the treatment under research, where the provision of leguminose Tricho-compost with a dosage of 50 tons / ha, equivalent to 250 g / 10 kg of soil is the best dosage on the growth and productivity of chilli plant. Keyword : Leguminose Tricho-compost, Capsicum annuum (L.), dosage and Productivity.